ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN (UKURAN PERUSAHAAN, RASIO PROFITABILITAS, RASIO LEVERAGE, DAN NET PROFIT MARGIN) TERHADAP PERATAAN LABA YANG TERDAFTAR DI BEI. - Nurkomariah Nurkomariah; Abdul Wahid Mahsuni; M. Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTThe purpose of this study is to find out and analyze company characteristics, namely company size, ROA, DER, NPM for income smoothing done by a company. The population in this study are manufacturing stock exchange for the period 2014-2017, totaling 150 companies. In the selection of samples, this study used a purposive sampling method, which obtained 27 companies as samples. The company’s financial statements have been published so that the required data is available and can be fulfilled. Testing the date in this study using the method of multiple regression analysis. Based on the test results it is known that simultaneously the variable size of the company. partially variable firm size, profitability ratio, leverage ratio does not affect while net profit margin, partially influence the income listed on the Indonesia stock exchange for the period 2014-2017. Keywords: company’s measure, profitability ratio, leverage ratio and net profit margin